(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2024)
The Corona Virus Disease (Covid-19) pandemic, the problems faced by various countries, is the main cause of education problems. In breaking the chain of transmission/spread of this virus, the Indonesian government has made various policies, one of which is about learning boldly. UNESCO (2020) implemented a national shutdown, leaving more than half of the world’s students unable to go to school. This study aims to determine the risk analysis of Low Back Pain (LBP) in students during courageous learning at STIK Dona Palembang in 2022. It was carried out in May - June 2022. This study was quantitative with a cross sectional design, the population of this study was STIK Dona students. Palembang returned 90 samples. Data collection and retrieval using a questionnaire. The results of statistical analysis using Chi-Square statistical tests and logistic regression showed that there was a significant relationship (p value < 0.05) for the variable stretching during college (0.000), length of time in college (0.038), physical activity (0.000), length of time virtual meeting (0.005), and body position during lecture (0.000). There is no relationship between sex variables (0.323). From the results of multivariate statistical tests, it was found that the dominant risk factor for LBP in students who survived studying was body position when studying (p = 0.001; OR = 8.328). It is recommended for the academic community to socialize to students during learning to maintain body posture when conducting virtual meeting lectures to teach how to sit in an ergonomic position.